Nonlinear finite element analysis and ADINA : proceedings of the 4th ADINA Conference, Massachusetts Institute of Technology, 15-17 June 1983 - Bathe, Klaus-Jurgen (Pergamon Press, 1983)
Nonlinear Finite Element Analysis and ADINA contains the proceedings of the Fourth ADINA Conference held at Massachusetts Institute of Technology on June 15-17, 1983.